Reptile enamel matrix proteins: Selection, divergence, and functional constraint. Issue 5 (2nd May 2019) - Alazem, Omar; Abramyan, John
Abstract: The three major enamel matrix proteins (EMPs): amelogenin (AMEL), ameloblastin (AMBN), and enamelin (ENAM), are intrinsically linked to tooth development in tetrapods. However, reptiles and mammals exhibit significant differences in dental patterning and development, potentially affecting how EMPs evolve in each group. In most reptiles, teeth are replaced continuously throughout life, while mammals have reduced replacement to only one or two generations. Reptiles also form structurally simple, aprismatic enamel while mammalian enamel is composed of highly organized hydroxyapatite prisms. These differences, combined with reported low sequence homology in reptiles, led us to predict that reptiles may experience lower selection pressure on their EMPs as compared with mammals. However, we found that like mammals, reptile EMPs are under moderate purifying selection, with some differences evident between AMEL, AMBN, and ENAM . We also demonstrate that sequence homology in reptile EMPs is closely associated with divergence times, with more recently diverged lineages exhibiting high homology, along with strong phylogenetic signal. Lastly, despite sequence divergence, none of the reptile species in our study exhibited mutations consistent with diseases that cause degeneration of enamel (e.g. amelogenesis imperfecta). Despite short tooth retention time and simplicity in enamel structure, reptile EMPs still exhibit purifying selection required to form durable enamel. Abstract : We calculated the percent identity between amino acid sequences of ameloblastin from various reptile groups. Crocodilians exhibit the highest sequence identity, while identity across squamates was substantially lower. Upon closer examination of the individual squamate clades, however, we found that identity values are actually much higher in snakes, with much of the variation existing between the various lizard infraorders. HIGHLIGHTS: Reptile enamel matrix proteins are under moderate purifying selection despite polyphyodonty and simple enamel structure. Sequence identity in reptile enamel matrix proteins exhibit correlation with divergence times in spite of differences in substitution rates. Reptile amelogenin operates under a distinct selection regime compared with ameloblastin and enamelin.